Time to healthcare seeking following the onset of symptoms among men and women attending a sexual health clinic in Melbourne, Australia - Farquharson, Rebecca M.; Fairley, Christopher K.; Abraham, Esha; Bradshaw, Catriona S.; Plummer, Erica L.; Ong, Jason J.; Vodstrcil, Lenka A.; Chen, Marcus Y.; Phillips, Tiffany R.; Chow, Eric P. F. (Frontiers in Medicine, 2022)
Background: Timely diagnosis and treatment of sexually transmitted infections (STIs) underpins their control by reducing the duration of infectiousness. There are currently limited data exploring healthcare seeking among individuals with STI symptoms. Methods: We analysed data on individuals reporting STI symptoms at the Melbourne Sexual Health Centre (MSHC) between August 2017 and December 2020. We calculated the time between symptom onset and clinic attendance by risk group for 13 STI diagnoses. We performed univariable and multivariable logistic regression to explore factors associated with delayed healthcare seeking (greater than seven days). Results: Among 7,032 symptomatic clinic attendances, the shortest time to healthcare seeking was among individuals diagnosed with gonococcal urethritis (median 3 days), and the longest was among individuals diagnosed with genital warts (median 60 days). Individuals diagnosed with gonococcal urethritis sought care earlier than individuals diagnosed with non-gonococcal urethritis (median 3 vs. 6 days, p<0.001), and individuals diagnosed with genital herpes sought care earlier than individuals diagnosed with primary syphilis (median 4 vs. 14 days, p<0.001). Men who have sex with men, and men taking human immunodeficiency virus pre-exposure prophylaxis (PrEP), were least likely to delay healthcare seeking. Both men and women who delayed healthcare seeking were more likely to live further from the clinic than those who did not delay their presentation (ptrend<0.001 [men] and ptrend=0.049 [women]). Conclusions: Improved local access to healthcare alongside targeted strategies to encourage early healthcare seeking among groups at increased likelihood of delay may reduce STI-associated morbidity and transmission.